1984
DOI: 10.1073/pnas.81.22.6993
|View full text |Cite
|
Sign up to set email alerts
|

Covalent bond formation between a DNA-cytosine methyltransferase and DNA containing 5-azacytosine.

Abstract: DNA containing 5-azacytosine (azaC) has previously been shown to be a potent inhibitor of DNA-cytosine methyltransferases. In this report, we describe experiments which demonstrate that azaC-DNA forms a covalent complex with Hpa II methylase, a bacterial enzyme that methylates the internal C of C-C-G-G sequences. The complex does not undergo detectable dissociation over at least 3 days and is stable to denaturation with NaDodSO4. After extensive digestion of the complex with DNase and phosphodiesterase, gel fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
313
0
9

Year Published

1988
1988
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 471 publications
(337 citation statements)
references
References 21 publications
9
313
0
9
Order By: Relevance
“…However, further analyses of all the histone termini (H2 to H4) are needed to confirm this hypothesis. 18,42 TSA has been reported to act synergistically with 5-aza to reactivate DNA methylation-silenced genes, [43][44][45][46] and Xiong et al have reported that histone deacetylase (HDAC) inhibitors decrease DNA methyltransferase-3B (DNMT3B) mRNA stability and down regulate de novo DNA methyltransferase. 47 To examine the relationship between histone modification and DNA methylation, we treated PANC1 cells with 5-aza and/or TSA.…”
Section: Discussionmentioning
confidence: 99%
“…However, further analyses of all the histone termini (H2 to H4) are needed to confirm this hypothesis. 18,42 TSA has been reported to act synergistically with 5-aza to reactivate DNA methylation-silenced genes, [43][44][45][46] and Xiong et al have reported that histone deacetylase (HDAC) inhibitors decrease DNA methyltransferase-3B (DNMT3B) mRNA stability and down regulate de novo DNA methyltransferase. 47 To examine the relationship between histone modification and DNA methylation, we treated PANC1 cells with 5-aza and/or TSA.…”
Section: Discussionmentioning
confidence: 99%
“…5-azaC is incorporated into newly synthesized DNA, where it covalently binds the methyltransferase that methylates cytidine in the newly synthesized DNA strand when 5-methyldeoxycytidyldeoxyguanosine is recognized on the parent strand (18). Pca and Hyd bind DNA (19)(20)(21), and may interfere with the action of the methyltransferase, resulting in hypomethylation of the newly synthesized strand.…”
Section: Discussionmentioning
confidence: 99%
“…These two drugs serve as cytidine analogs that are incorporated into DNA, where they form covalent bonds with DNMT, leading to depletion of functional enzyme. 30,31 More recent studies have also shown that decitabine induces a rapid and selective degradation of DNMT1 through the proteasomal protein-degradation pathway. 32 Recent studies showed that induction of HbF by decitabine is associated with a decrease in DNA methylation at the promoters of the γ-globin genes in erythroid bone marrow cells in baboons and patients with SCD.…”
Section: Mechanisms Of Pharmacologicalmentioning
confidence: 99%